Does the quality of tourist shuttles influence revisit intention through destination image and satisfaction? The case of Macao. (September 2017) - Loi, Lawrence Teng Iat; So, Amy Siu Ian; Lo, Iris Sheungting; Fong, Lawrence Hoc Nang
Abstract: Transportation is a necessity for tourists at a destination. However, empirical evidence of the impact of quality of tourist shuttles on intention to revisit a destination has been lacking. This study contributes to the tourism literature by linking quality of tourist shuttles with intention to revisit a destination and by examining the underlying mechanism. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the analysis of data collected from 282 inbound tourists in Macao reveals that quality of tourist shuttles predicts intention to revisit through two mediators - destination satisfaction and image. The results also show that destination image predicts intention to revisit through destination satisfaction. The findings suggest that destination marketers should strive to maintain high quality tourist shuttle service, specifically in the areas of staff service, efficiency, punctuality, and safety.